Antimicrobial Activity of Tulsi (Ocimum tenuiflorum) Essential Oil and Their Major Constituents against Three Species of Bacteria - Yamani, Hanaa A.; Pang, Edwin C.; Mantri, Nitin; Deighton, Margaret A. (Frontiers in Microbiology, 2016)
In recent years scientists worldwide have realized that the effective life span of any antimicrobial agent is limited, due to increasing development of resistance by microorganisms. Consequently, numerous studies have been conducted to find new alternative sources of antimicrobial agents, especially from plants. The aims of this project were to examine the antimicrobial properties of essential oils distilled from Australian-grown Ocimum teniflorum (Tulsi), to quantify the volatile components present in flower spikes, leaves and the essential oil, and to investigate the compounds responsible for any activity. Broth micro-dilution was used to determine the minimum inhibitory concentration (MIC) of Tulsi essential oil against selected microbial pathogens. The oils, at concentrations of 4.5% and 2.25% completely inhibited the growth of Staphylococcus aureus (including MRSA) and Escherichia coli, while the same concentrations only partly inhibited the growth of Pseudomonas aeruginosa. Of 54 compounds identified in Tulsi leaves, flower spikes or essential oil, three are proposed to be responsible for this activity; camphor, eucalyptol and eugenol. Since S. aureus (including MRSA), P. aeruginosa and E. coli are major pathogens causing skin and soft tissue infections, Tulsi essential oil could be a valuable topical antimicrobial agent for management of skin infections caused by these organisms.